A structured system's view of an intelligent tutoring system based on inquiry teaching approach - Wong, Lung Hsiang. (2009)
This thesis describes a research effort that has been motivated by a keen desire to bridge the gap between educational research and computational science research. It consists of three portions: (1)To study the feasibility of computerizing the inquiry teaching method of [Collins and Stevens, 1982a]; (2)To re-interpret the ITS architecture in general, and the TAP architecture in particular, in terms of control theory; (3)To propose a new version of TAP architecture whose instructional planning mechanism strictly adheres to the definition of "adaptive control".